Training for Designing Automatic Temperature Detector Based on Arduino Uno using Tinkercad to Improve Teacher Competence at MTS Tarbiyatul Falah - Alam, Syah; Surjati, Indra; Sari, Lydia; Iznih; Alga Maulana, Gusti (LPPM Universitas Muhammadiyah Tasikmalaya, 2025)
MTS Tarbiyatul Falah is a junior high school educational institution that organizes a madrasah-level education program that follows the curriculum set by the Ministry of Education and Culture of the Republic of Indonesia where one of its extracurricular activities is the introduction of basic electronics to students. For that, the urgency of this community service activity is to provide training to teachers at MTS Tarbiyatul Falah to be able to design and realize a temperature control circuit based on Arduino Uno. The purpose of this community service activity is to provide training in the use of tinkercad for basic Arduino programming in order to improve teachers' knowledge in providing materials, especially in the field of electronics. From this activity, the ability and understanding of the training participants increased from 56 to 90 based on the pre-test and post-test. In addition, the satisfaction of the training participants was also very high as shown based on the results of the questionnaire where the average satisfaction was 95%. Therefore, this activity is very useful especially for improving the ability of MTS teachers in designing electronic circuits using Arduino Uno.